INFLUENCE OF LODGING AND NITROGEN RATE ON THE YIELD AND YIELD ATTRIBUTES OF OILSEED RAPE (BRASSICA NAPUS L). (Biological Sciences - PJSIR, 2022)
Effects oflodging and nitrogen rate were studied in a field trial of oilseed rape Brassicanapus L. Lodging decreasedseed yield (16%) compared with a frame-raised crop. The yield decreased because of a significant reduction of each ofthe yield components coupled with a reduced plant population caused by stem breakage at the ground level. Lodgingalso reduced the final crop dry weight and harvest index. Seed yield also decreased from the 400 kg ha' of nitrogenapplication compared with 200 kg ha'. A general decrease in pod number m", seed number pod" and seed weight causedlower yields. The use of 400 kg ha -I of nitrogen changed the contribution of terminal raceme and individual brancheswith respect to seed yield. Seed nitrogen content and nitrogen yield increased at the 400 kg ha', lowering both seed oilcontent and oil yield.